Deteksi Cemaran Streptococcus spp. dan Escherichia coli Pada Lawar Plek Di Desa Sukawati, Kecamatan Sukawati, Kabupaten Gianyar - Ni Kadek Dwi Putri Yulia Pramesti Kastawa; I Desak Putu Kartika Pratiwi; Sayi Hatiningsih (Study Program of Food Technology, Faculty of Agricultural Technology, Udayana University, 2026)
Lawar plek is a traditional Balinese food, especially in the Sukawati area, Kabupaten Gianyar. Lawar plek is made from a mixture of vegetables, chopped raw pork, spices, and the addition of raw pork blood. This lawar plek is susceptible to being contaminated with pathogenic bacteria due to the addition of raw meat and blood and a lack of hygiene and sanitation. This research aimed to determine the level of contamination of Streptococcus spp. and Escherichia coli in lawar plek in Sukawati Village, Kabupaten Gianyar. Samples were collected using the purposive sampling method. A total of six restaurants in Sukawati Village that met the sample criteria were included in this study and were coded RM1, RM2, RM3, RM4, RM5, and RM6. The lawar plek samples used in this research were taken at 11.00 and 14.00 WITA. Streptococcus spp. was detected by observing colony growth on Blood agar media, Gram staining, and catalase test, while E. coli contamination was carried out by observing the development of green metallic sheen colonies on Eosin Methylene Blue Agar (EMBA), and coliform contamination was detected through MPN calculations using media Lactose Broth (LB). The results showed that four samples (33.3%) of lawar plek were positive for containing Streptococcus spp. The E. coli test results showed that 100% of lawar plek did not meet the requirements for meat food without heat treatment (1,8 APM/gram). The detection of Streptococcus spp. and E. coli in the lawar plek samples indicates that hygiene and sanitation practices in the food processing and serving process are not being implemented, so further supervision needs to be carried out to reduce the occurrence of pathogenic bacteria contamination.